RAF-1 promotes survival of thyroid cancer cells harboring RET/PTC1 rearrangement independently of ERK activation. (5th November 2015) - Castro, Lisandra; Alves, Sara; Chaves, Susana R.; Costa, José Luis; Soares, Paula; Preto, Ana
Abstract: Thyroid cancer (TC) is frequently associated with BRAF or RAS oncogenic mutations and RET/PTC rearrangements, with aberrant RAF-MEK-ERK and/or PI3K pathway activation. BRAF underlies ERK activation in most TC cells, but not in TPC-1 cells with RET/PTC1 rearrangement. Here, we show that depletion of RAF-1, a RAF family member with a poorly defined role in TC, decreases proliferation and increases apoptosis in TPC-1 cells and, less significantly, in cells harboring a BRAF V600E or HRAS G13R mutations, but without affecting ERK activation. We further demonstrate that constitutive activation of ERKs in TPC-1 cells is not caused by mutations in 50 oncogenes and tumor suppressors prone to activate the ERK pathway, or affected by inhibition of BRAF, MEK1/2 or PI3K. Our data indicate that RAF-1 is important for the survival of TPC-1 cells independently of the classical MEK1/2-ERK activation, offering new perspectives on RET/PTC signaling and for the therapy of thyroid cancers. Highlights: The role of RAF-1 in thyroid cancer cell survival depends on the genetic background. Thyroid cancer cells with RET/PTC1 bypass RAF-1 or BRAF for ERK activation. RAF-1 might constitute a good molecular target in thyroid cancers with RET/PTC1.